Herbal Compatibility of Ginseng and Rhubarb Exerts Synergistic Neuroprotection in Cerebral Ischemia/Reperfusion Injury of Rats - Yang, Wen-Ting; Wang, Yong; Shi, Yi-Hua; Fu, Huan; Xu, Zhen; Xu, Qing-Qing; Zheng, Guo-Qing (Frontiers in Physiology, 2019)
Objective: Ischemic stroke is a complex multifactorial disease caused by interactions among polygenetic, environmental, and lifestyle factors with limited effective treatments. Multi-herbal formulae have long been used for stroke via herbal compatibility under traditional Chinese medicine wisdom; however, there is still lack of evidences due to their unimaginable complexity. Herbal pairs represent the simplest and basic features of multi-herbal formulae, which are of great significance for clarifying herbal compatibility. Here, we aim to investigate the neuroprotective effects of herbal compatibility of Ginseng and Rhubarb on cerebral Ischemia/Reperfusion (I/R) injury model of rats. Methods: Male adult SD rats were randomly divided into sham group, normal saline (NS) group, Ginseng group, Rhubarb group and Ginseng + Rhubarb (GR) group, Carbenoxolone (CBX, gap junction specific inhibitor) group, and GR+ CBX group. Each group was further assigned into 4 subgroups according to ischemic time (6h, 1d, 3d, and 7d). The cerebral I/R injury model was established according to modified Zea Longa method. Neurological Deficiency Score (NDS) was assessed by the Zea-Longa scale; cerebral infarction area was detected by TTC (2,3,5-Triphenyltetrazolium chloride) staining; and the expression of Connexin-43 (Cx43) and Aquaporin-4 (AQP4) were detected based on immunofluorescence technique and Quantitative Real-time-PCR. Results: Compared with I/R group, both the independent and combined use of Ginseng and Rhubarb can significantly improve NDS (P < 0.05), decrease the percentage of cerebral infarction area around infarction penumbra (P < 0.05) and down-regulate the expression of Cx43 and AQP4 after I/R injury (P < 0.05). The GR had more significant effects than that of Ginseng and Rhubarb (P<0.05). Compared with GR group, GR+ CBX group significantly improved in NDS (P < 0.05), and decreased the percentage of cerebral infarction area (P < 0.05) and expression of Cx43 and AQP4 protein (P < 0.05) Conclusion: The herbal compatibility of ginseng and Rhubarb exerts synergistically neuroprotective function during acute cerebral I/R injury, mainly through reducing the expression of Cx43 and AQP4.